Virtual Slice Extraction Based on Hermite Interpolation - TIAN Qi-chuan; CHEN Bin; WANG Da-shen; FAN Wen-guang (Institute of Advanced Engineering and Science, 2012)
Owing to the one-time scanning direction’s oneness and the limited slices’ number of the current CT imaging equipment, we propose an extraction algorithm of any angle virtual slice on 3D medical image based on the Hermite interpolation. In view of the large slice thickness, we first use the Hermite interpolation algorithm to interpolate the data between layers, and then by setting a virtual plane of normal vector and the interior point, combined with improved three-dimensional linear interpolation algorithm for image sequence to be cut we obtain a virtual slice, finally we observe the extraction with a three-dimensional reconstruction of the virtual slices. Experimental result shows that the extracted virtual slice is close to the actual slice, it can be used for computer-aided diagnosis, clinical diagnosis, and it compensates for the CT imaging equipment on the lack of imaging. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1409